Association of chronic kidney disease with all-cause mortality in patients hospitalized for atrial fibrillation and impact of clinical and socioeconomic factors on this association - Bao, Min-qiang; Shu, Gui-jun; Chen, Chuan-jin; Chen, Yi-nong; Wang, Jie; Wang, Yu (Frontiers in Cardiovascular Medicine, 2022)
Background Atrial fibrillation (AF) and chronic kidney disease (CKD) often co-occur, and many of the same clinical factors and indicators of socioeconomic status (SES) are associated with both diseases. The effect of the estimated glomerular filtration rate (eGFR) on all-cause mortality in AF patients and the impact of SES on this relationship are uncertain. Materials and methods This retrospective study examined 968 patients who were admitted for AF. Patients were divided into four groups based on eGFR at admission: eGFR-0 (normal eGFR) to eGFR-3 (severely decreased eGFR). The primary outcome was all-cause mortality. Cox regression analysis was used to identify the effect of eGFR on mortality, and subgroup analyses to determine the impact of confounding factors. Results A total of 337/968 patients (34.8%) died during follow-up. The average age was 73.70 ± 10.27 years and there were 522 males (53.9%). More than 39% of these patients had CKD (eGFR < 60 mL/min/1.73 m2), 319 patients with moderately decreased eGFR and 67 with severely decreased eGFR. After multivariate adjustment and relative to the eGFR-0 group, the risk for all-cause death was greater in the eGFR-2 group (HR = 2.416, 95% CI = 1.366–4.272, p = 0.002) and the eGFR-3 group (HR = 4.752, 95% CI = 2.443–9.242, p < 0.00001), but not in the eGFR-1 group (p > 0.05). Subgroup analysis showed that moderately to severely decreased eGFR only had a significant effect on all-cause death in patients with low SES. Conclusion Moderately to severely decreased eGFR in AF patients was independently associated with increased risk of all-cause mortality, especially in those with lower SES.